Are Osha Health Inspections Effective? A Longitudinal Study in the Manufacturing Sector - Gray, Wayne B.; Jones, Carol Adaire (The Review of Economics and Statistics, 1991)
Wayne B. Gray, Carol Adaire Jones, Are Osha Health Inspections Effective? A Longitudinal Study in the Manufacturing Sector, The Review of Economics and Statistics, Vol. 73, No. 3 (Aug., 1991), pp. 504-508